(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Purpose/Aim:- The aim of the present research study was to study the facilitating factors of pharmaceutical digital marketing challenges and opportunities in the contemporary context. The role of digital marketing plays a crucial role for better interaction, cost-effectiveness, to build a relationship between physicians and people with personalized care. Research Methodology/Approach/Design:- It is a descriptive research design, the data collected through structured closed ended questionnaire with a sample of 50 from undergraduates and post-graduates. Statistical tools:- Applied both descriptive and inferential statistics like: Mean, SD, ANOVA and Chi-Square test to assess the opinion of the respondents.Findings:-The outcome of the research witnessed that the majority of the respondents agreed that Pharma products should be produced for specific purpose, availability of website and online content, usage of whatsApp, twitter, Instagram other platforms plays a crucial role to interact with the customers, recommendations by experts, users, building loyalty and trust plays a significant role to interact with the customers and to increase the sales of the business. Further, product differentiations, advertisements, building the databases are the essential aspects to strengthen the digital marketing. Novelty:- The concept which is novel, as few literatures are available on digital pharma marketing in the contemporary scenario. Generalizability:- The outcome of the research can be generalized under any phenomenon where need arises to strengthen the pharma digital marketing strategies in India. Originality:- The present research on antecedents of digital marketing strategies has not been copied from any source. Type of Research:-It is a descriptive research study where it has taken the advantage of both descriptive and inferential statistics.